Constraints to small and medium-sized enterprises development in Bangladesh: results from a cross-sectional study - Islam, Md. Shahidul; Hossain, Md. Faruk (The European Journal of Applied Economics, 2018)
Small and Medium Enterprises (SMEs) are the significant contributor to the Bangladesh economy as they have the competency to create higher employment, improve local technology, and create ground for the future sustainable industrialization and corporate sectors. The aim of this study is to identify major constraints faced by the SMEs in Bangladesh. A cross-sectional study was conducted in Narsingdi Municipality, Bangladesh and social survey method was applied to collect the data. Two-stage cluster sampling method was utilized to select respondents and data were collected through face-to-face interview. Principal Component Analysis (PCA) was used to determine significant constraints to SMEs. The study found that poor infrastructure and electricity supply are the main constraints to the development of SMEs. Limited access to credit, lack of proper business knowledge and plan, high domestic market competition, lack of skilled manpower and technology, and high cost of raw materials and equipment are the major constraints next to main constraint.